2014
DOI: 10.2174/1871527313666141023120843
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potent Caspase-3 Inhibitors for Treatment of Multi- Neurodegenerative Diseases Using Pharmacophore Modeling and Docking Approaches

Abstract: Neurodegenerative disorders are due to excessive neuronal apoptosis and the caspase-3 plays a key role in the apoptotic pathway. The caspase-3 inhibition may be a validated therapeutic approach for neurodegenerative disorders and an interesting target for molecular modeling studies using both Ligand and structure based approaches. In view of the above we have generated the Ligand based pharmacophore model using the Discovery studio 2.0 software. In addition to this a structure based approach has been used to v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Abnormalities in brain functions, such as memory, movement, and cognition, result in neurodegenerative disorders [4]. Various studies have reported that neurodegeneration is prompted rapidly by the combination of progressive neuronal loss and dysfunction [5, 6]. A common feature of many NDs is an extended time course until a sufficient amount of abnormal protein forms into aggregates, in addition to many symptoms over years with increasing disability [7].…”
Section: Introductionmentioning
confidence: 99%
“…Abnormalities in brain functions, such as memory, movement, and cognition, result in neurodegenerative disorders [4]. Various studies have reported that neurodegeneration is prompted rapidly by the combination of progressive neuronal loss and dysfunction [5, 6]. A common feature of many NDs is an extended time course until a sufficient amount of abnormal protein forms into aggregates, in addition to many symptoms over years with increasing disability [7].…”
Section: Introductionmentioning
confidence: 99%
“…In all probability, compound 11 as a celastrol derivative could induce apoptosis by inducing the activation of caspases. The caspase-3 plays a key role in the apoptotic pathway 24 . To confirm this speculation, in this text, docking simulation was performed to position compound 11 into the caspase-3 (1GFW) active site to determine the probable binding model ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Based on our previous studies on approaches to indirect drug design [32,33] and in the field of neurodegenerative disease [33] we decided to focus on caspase 8 inhibitors. Molecules reported in the literature were collated [26], but biological activity data did not exhibit the required 3 log unit variation necessary to develop a quantitative pharmacophore model using the Hypogen module in Catalyst software.…”
Section: Methodsmentioning
confidence: 99%